Hydrogen System Design Methodology for Autonomous Houses in Central-East Europe - István Ervin Háber; Erzsébet Cserta; Virag Meszaros (Chemical Engineering Transactions)
As part of the energy transition, the building sector must be revolutionized to reach the goal of carbon neutrality since it is responsible for 3 Gt of CO2 emission worldwide every year. Energy storage capacities, which could help in the spread of renewables – are still at a very low level. Hydrogen is considered a solution for seasonal hydrogen storage, but only a few examples exist still worldwide to showcase the technology. The residential sector is more underrepresented in this manner. Therefore, the number of good practices should be higher to give examples to architects and engineers. In this paper, a design methodology is presented, which can help to identify and size the system components for autonomous (i.e., grid-independent) homes. An opportunity is given to estimate the cost of the whole complex electrical system. As the heat loss factor of buildings and the energy use of residents can be determined as part of the energy label certification, the sizing of the renewable energy equipment is an iterative process. For that, more grade system losses have to be taken into consideration. The result of this study is a numerical formula that gives the needed component properties. This offers stakeholders and real estate developers an easy tool to predesign their systems in the early stages of development.